UNFOLDING THE POTENTIAL OF E-PORTFOLIOS FOR ASSESSMENT OF METACOGNITIVE SKILLS IN HIGHER EDUCATION - Gull Sher, Sameer; Mahmood, Aisha (JELM, 2025)
This qualitative research looks at how higher education students feel about using ePortfolios for metacognitive progress and assessment, specifically within the context of project-based learning (PBL). A total of seven participants from the higher education context were recruited for this research. To gather data, interviews were conducted in a semi-structured manner, as well as the thematic analysis employed to explore the interview transcripts, resulting in the identification of four key themes. The results show that ePortfolios have a important influence on the improvement of metacognitive abilities, offer a thorough assessment in comparison to other techniques, present certain difficulties and disadvantages, and are appreciated by learners in higher education. These observations add to the expanding body of research on ePortfolios and their role in supporting metacognitive development within the context of PBL. The implications of these results for educational practice and policy include the integration of ePortfolios to enhance student engagement, critical thinking, and self-regulation in PBL environments. Furthermore, this study suggests the need for larger-scale research to validate and expand upon these findings, as well as investigating the perspectives of educators and administrators. Overall, this research provides valuable insights into the advantages and potentiality of using ePortfolios for evaluating metacognition abilities in higher education, particularly in project-based learning.